First Principle Computational Studies On The Electronic Structure Of Muonated Κ-(Bedt-Ttf)2cu[N(Cn)2]Cl And Κ-D8-(Bedt-Ttf)2cu[N(Cn)2]Br - Baseri, Dang Fatihah Hasan (2022)
κ-(BEDT-TTF)2Cu[N(CN)2]Cl and κ-d8-(BEDT-TTF)2Cu[N(CN)2]Br are organic magnetic materials with potential applications in spintronics. The amount of μSR data on this structure has increased rapidly and continues to appear over time. The unpaired electrons are usually located throughout the dimer and not around specific atoms that can affect the magnetic properties of the system. In principle, the long-range order of magnetic moments that configures the magnetic structure of the system is still unclear and further research is needed. To complete the μSR study, Density Functional Theory (DFT) calculations were carried out to investigate the electronic structure in high spin and antiferromagnetic (AFM) states as well as to observe the type of magnetism present in this compound.